Gaining Insight into Service Issues in the Cafe Industry through the Implementation of the SERVQUAL Method - Reni Respita; Eni Eni; Yuda Dewanta (TourEcon: International Journal of Tourism and Economic Studies, 2024)
This research aims to gain a deeper understanding of service problems in the cafe industry through the application of the SERVQUAL method. This method is used to measure customer perceptions of service quality and identify areas where improvement is needed. Data was collected through surveys and analyzed using a statistical approach. The research results highlight certain aspects of cafe service that need to be improved, such as service responsiveness, product reliability, guarantees, empathy, and physical evidence elements. The implications of this research are to help cafe owners to improve customer experience and maintain a competitive advantage in this industry.